Heterogeneous acid-base organocatalyst for cascade deacetalisation-knoevenagel condensations - Chhetri, Ashis; Maibam, Ashakiran; Maniam, Subashani; BabaRao, Ravichandar; Wilson, Karen; Lee, Adam F.; Mitra, Joyee (ChemSusChem, 2024)
Multifunctional heterogeneous catalysts are an effective strategy to drive chemical cascades, with attendant time, resource and cost efficiencies by eliminating unit operations arising in normal multistep processes. Despite advances in the design of such catalysts, the fabrication of proximate, chemically antagonistic active sites remains a challenge for inorganic materials science. Hydrogen-bonded organocatalysts offer new opportunities for the molecular level design of multifunctional structures capable of stabilising antagonistic active sites. We report the catalytic application of a charge-assisted, hydrogen-bonded crystalline material, bis(melaminium)adipate (BMA), synthesised from melamine and adipic acid, which possesses proximate acid-base sites. BMA exhibits high activity for the cascade deacetalisation-Knoevenagel condensation of dimethyl acetals to form benzylidenemalononitriles under mild conditions in water; BMA is amenable to large-scale manufacture and recycling with minimal deactivation. Computational modelling of the melaminium cation in protonated BMA explains the observed catalytic reactivity, and identifies the first demethoxylation step as rate-limiting, which is in good agreement with time-dependent 1H NMR and kinetic experiments. A broad substrate scope for the cascade transformation of aromatic dimethyl acetals is demonstrated.
Keywords: Antagonistic acid-base sites; Charge-assisted hydrogen bonding; Chemical cascade; organocatalysis; Sustainable catalysis